ANALISIS KEMAMPUAN PROSES PELAPISAN POLYUREA PADA ACRYLIC DENGAN KETEBALAN TERTENTU TERHADAP SIFAT MEKANIK - Jason Arie Putra; Erwin Siahaan; Steven Darmawan (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Coating became quite common. The coating serves as a conduit of color and also to cover the base material. Polyurea coating is a new innovation in the field of industry, so far polyurea coatings are used to coat the walls of the building and also the roof of the building to tackle the problem of leakage. This study explains how large the influence of the Polyurea coatings to acrylic. In this study which is distinguished by variations in thickness 3mm acrylic, 5mm and 8mm. This study also discusses the tensile resilience and resistance to shock loads. The purpose of this study was to determine how much influence the Polyurea coatings by comparing with Polyurea acrylic coated and uncoated. As an example of the results obtained from tensile tests that 3mm acrylic coated and uncoated increased by 39.6% acrylic 5mm by 0.66% and 1.65% acrylic 8mm. Polyurea coatings can not deliver maximum results on specimens that have smooth surfaces, so that we can see that in every test carried downhill result.